Sustainable Tourism Development in the Village of Rancabango: Maintaining and Developing Local Wisdom - Juju Jumaedi (Enrichment : Journal of Management, 2021)
The tourism industry is one of the largest industries in the world. The tourism industry can absorb a large number of workers, be able to increase income and the economy and can make a large contribution to a country. This has prompted many countries to be interested in developing tourism as a development sector, especially for developing countries including Indonesia. As one of the largest industries in the world, tourism development is expected to be able to improve the economy so that it can improve the welfare of the people where tourism is developed. In addition, tourism can provide benefits for the preservation of nature, culture and the environment and is sustainable, such as sustainable tourism management in the Garut Regency area, precisely in the village of Rancabango. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that, sustainable tourism development is a development concept that pays attention to elements that are not only the potential of the village physically, but also involve ecology, culture and ecology so that the benefits of development continue. sustainable because the building blocks of development are well maintained. The concept of sustainable development is still a popular issue and goal in this era because the concept of sustainable economics does not only manage the economic system, but considers environmental aspects. One of them is Village Owned Enterprises. BUMDES is a pillar of village economic development and development in responding to the challenges and potentials of the currently developing economic system. BUMDES is a forum managed by the Village and/or inter-Village cooperation to manage and develop activities in the economic field while carrying out an orientation to public services and social development for improving the welfare of rural communities